The Effect of Mind Mapping toward Creative Thinking and Learning Outcomes of Pre-Service Elementary School Teacher - Riswanti, Nova; Prehadini, Tampi; Erviana, Vera Yuli (FKIP Universitas Lampung, 2023)
The Effect of the Application of the Mind Mapping Method on Creative Thinking Skills and Learning Outcomes of PGSD Students. Objective: this study is to determine the effect of the application of mind mapping methods on the ability to think creatively and learning outcomes of PGSD UAD students. Method: This research is a quantitative research with the type of research type -Experimental Design One Group Pretest-Posttest. The sample used in this study was PGSD Semester 2 students in the Advanced Social Studies course totaling 29 students consisting of 24 women and 5 men. Pretest and posttest test questions developed by researchers were given to students to obtain research data. Then analyzed using t-test with a significant level of 0.05. Findings: The application of mind mapping method improves creative thinking ability and learning outcomes. Conclusion: There is a significant effect on the learning outcomes of UAD students using the mind mapping learning method. Conclusion: There is a significant influence on the learning outcomes of UAD students using the mind mapping learning method. Keywords: creative thinking, mind mapping, social studies learning.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202340